2013
DOI: 10.1007/s00125-013-2846-8
|View full text |Cite
|
Sign up to set email alerts
|

Mouse strain-dependent variation in obesity and glucose homeostasis in response to high-fat feeding

Abstract: Aims/hypothesis Metabolic disorders are commonly investigated using knockout and transgenic mouse models. A variety of mouse strains have been used for this purpose. However, mouse strains can differ in their inherent propensities to develop metabolic disease, which may affect the experimental outcomes of metabolic studies. We have investigated straindependent differences in the susceptibility to diet-induced obesity and insulin resistance in five commonly used inbred mouse strains (C57BL/6J, 129X1/SvJ, BALB/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
302
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(356 citation statements)
references
References 48 publications
46
302
2
6
Order By: Relevance
“…Consistent with the Balb genetic background of these mice, HFD did not affect glucose tolerance or the insulin response of WT mice, as determined by GTTs and ITTs (Fig. 3i,j) [22]. However, Lbp-null mice exhibited marked glucose intolerance and reduced insulin sensitivity on both a standard diet and HFD.…”
Section: Resultssupporting
confidence: 73%
“…Consistent with the Balb genetic background of these mice, HFD did not affect glucose tolerance or the insulin response of WT mice, as determined by GTTs and ITTs (Fig. 3i,j) [22]. However, Lbp-null mice exhibited marked glucose intolerance and reduced insulin sensitivity on both a standard diet and HFD.…”
Section: Resultssupporting
confidence: 73%
“…2c and 6c). A recent report documented the skeletal muscle and liver lipid accumulation in five different strains of mice fed a HFD (Montgomery et al 2013). In accordance with the present study, this previous study (Montgomery et al 2013) also identified strain-specific differences in organ lipid accumulation between BALB/c and C57BL/6 mice.…”
Section: Discussionsupporting
confidence: 92%
“…Overexpression of Hsp72 does not alter heart size, insulin-stimulated glucose clearance, or fatty acid oxidation rate in Hsp72 BALB/c mice As our previous work on Hsp72 overexpression in skeletal muscle was predominantly carried out in mice on a BALB/c background (Chung et al 2008;Henstridge et al 2014) and considering different mouse strains can have different total levels and rates of lipid accumulation (Kahle et al 2013;Montgomery et al 2013), we also conducted analyses on the hearts from these mice. Similar to the Hsp72 Tg mice on the C57BL/6J background, no difference in heart mass was observed (Supp Fig.…”
Section: Hsp72mentioning
confidence: 99%
“…Although fatty liver develops in response to a wide diversity of physiological perturbations, these perturbations result in a similar metabolic phenotype that includes insulin resistance, hyperglucagonemia, hypertriglyceridemia, hyperglycemia and hyperketonemia. Of note, mouse models that lack hepatic lipid accumulation retain insulin sensitivity during obesity (Chen et al 2002, Franckhauser et al 2002, Haemmerle et al 2006, Montgomery et al 2013. Similarly, metabolically healthy obese humans are insulin sensitive with significantly less liver fat accumulation than obese, insulin resistance individuals (Stefan et al 2008, T & Gonzalez FJ 1998 …”
Section: Resultsmentioning
confidence: 99%